25 years of SEA: personal reflections on recent progress, current status and future prospects. Issue 1 (2nd January 2023) - Sadler, Barry; Verheem, Rob
ABSTRACT: 2021 marked the 25 th anniversary of the publication of our report 'SEA – status, challenges and future directions'. This report was part of an international study of the effectiveness of environmental assessment by a consortium of countries and organisations. In recognition of the anniversary, the NCEA has placed a digital version of the report, making it widely available through the internet for the first time (www.eia.nl ). The report documents the state of SEA practice at a key stage of process development and provides a benchmark against which subsequent progress can be reviewed. Using the report as a baseline, we take stock of the course of SEA development over the last quarter century and its bearing on the state of practice today.